Brief Reports - HER2 Amplification and HER2 Mutation Are Distinct Molecular Targets in Lung Cancers. Issue 3 (March 2016) - Li, Bob T.; Ross, Dara S.; Aisner, Dara L.; Chaft, Jamie E.; Hsu, Meier; Kako, Severine L.; Kris, Mark G.; Varella‐Garcia, Marileila; Arcila, Maria E.
ABSTRACT : Introduction: : Human epidermal growth factor receptor 2 gene ( HER2 [also known as ERBB2 ]) alterations have been identified as oncogenic drivers and potential therapeutic targets in lung cancers. The molecular associations of HER2 gene amplification, mutation, and HER2 protein overexpression in lung cancers have not been distinctly defined. To explore these associations, Memorial Sloan Kettering Cancer Center and the University of Colorado combined their data on HER2 alterations in lung cancers. Methods: : Tumor specimens from 175 patients with lung adenocarcinomas and no prior targeted therapy were evaluated for the presence of HER2 amplification and mutation and HER2 protein overexpression. Amplification was assessed by fluorescence in situ hybridization (FISH) and defined as an HER2‐to‐chromosome enumeration probe 17 ratio of at least 2.0. Mutation was assessed by fragment analysis, mass spectrometry genotyping, and Sanger sequencing. Overexpression was assessed by immunohistochemical (IHC) staining. The frequencies of HER2 amplification and mutation and HER2 overexpression were calculated and their overlap examined. Results: : HER2 amplification was detected by FISH in 5 of 175 cases (3%). HER2 mutation was detected in 4 of 148 specimens (3%), including three identical 12–base pair insertions (p.A775_G776insYVMA) and a 9–base pair insertion, all in exon 20. None of the HER2 ‐mutant cases was amplified. HER2 overexpression (2+ or 3+) on IHC staining was not detected in the 25 specimens available for testing, and negative IHC staining correlated with the negative results according to FISH. Conclusions: : HER2 mutations are not associated with HER2 amplification, thus suggesting a distinct entity and therapeutic target. HER2 ‐positive lung cancer may not be an adequate term, and patient cohorts for the study of HER2‐targeted agents should be defined by the specific HER2 alteration present.